Dietary Knowledge and Physical Activity Level as Correlates of Excess Weight Categories Among Grade VIII Students: A Cross-Sectional Study at SMPN 271 Jakarta - Chairurizki, Dinda; Dinaryanti, Ratna Sari; Rostarina, Nila; Ramadhan, Gaung Eka (Jurnal Kesehatan dan Kedokteran, 2026)
Adolescent overweight is increasing in many low- and middle-income settings and is shaped by diet-related knowledge, daily activity patterns, and the school environment. Objective: This study aimed to examine the association between students’ dietary knowledge and physical activity level with excess weight categories among Grade VIII students at SMPN 271 Jakarta in 2024. Methodology: A quantitative cross-sectional analytic study was conducted among 183 Grade VIII students selected using stratified random sampling. Dietary knowledge was measured using a validated 11-item questionnaire (Cronbach’s alpha = 0.931) and categorized as good, moderate, or poor. Physical activity was assessed using the WHO Global Physical Activity Questionnaire (GPAQ) and categorized into low or moderate levels. Associations between dietary knowledge and excess weight categories, and between physical activity and excess weight categories, were tested using the chi-square test (p < 0.05). Findings: Almost half of students had good dietary knowledge (48.1%), while most reported low physical activity (89.1%). Dietary knowledge level was significantly associated with excess weight category (p = 0.004), and physical activity level was also significantly associated with excess weight category (p = 0.004). Implications: The findings support integrated school-based interventions that combine nutrition education with strategies to increase daily physical activity and reduce sedentary routines, including optimizing the school food environment and expanding opportunities for active breaks and extracurricular activities. Originality: This study provides context-specific evidence from an urban junior high school in Jakarta by assessing dietary knowledge and physical activity concurrently in relation to excess weight categories, offering practical insights for designing comprehensive school health programs targeting adolescents.